„Mało kto z nas wszystkich jeszcze żyjących daje mi to poczucie ciągłości polskiej […] literatury XX wieku”. Listy Teodora Parnickiego do Aleksandra Wata - Gorliński-Kucik, Piotr (Śląskie Studia Polonistyczne, 2013)
The collection of ten letters written by Teodor Parnicki to Aleksander Wat between 1942 and 1961 is included here. The first two letters concern the article of the author of Bezrobotny Lucyfer in “Polska”, a weekly published in Kujbyszew, the editor of which was Parnicki. The remaining letters were sent by the author of Tylko Beatrycze from Mexico to Italy, and concerned the issue of publishing the novel Srebrne orły in Silva Editore, which eventually did not happen.